Development of a Solar Supplemented Chick Brooding System in Port Harcourt, Nigeria - Zibokere, D S; Akor, A J (Journal of Agricultural Engineering, 2001)
The design and development of a solar heated chick brooding facility is presented in which air is used as heat transfer fluid and pebbles as storage medium. With a collector (flat plate) area of 1.35 mÂ² and rock-bed storage volume of 2mÂ³ the solar heating system was constructed and tested for five stockings in two years along with a conventional system based on kerosene fuel heating. During testing 100 chicks (at day-old) were stocked per system per period. The solar brood system recorded 50% lower chick mortality within the 28-day brooding period as compared to the conventional brooding facility. The average liquid fuel saving was 68% over the non-solar brooder. The solar brood system showed significant (p = 0.05) improvement in all the biological performance parameters (body weight, feathering-out time and feed conversion). The solar brooding facility presented a practical means of utilizing solar energy for chick brooding in place of kerosene in Port Harcourt, Nigeria.